Inventory of the Oriental Manuscripts of the Library of the University of Leiden. Manuscripts OR. 23001 - OR 24000 registered in Leiden University Library in the Period between August 1992 and November 1997 - Witkam, Jan Just (Ter Lugt Press, 2007)
OR 23291 : kitab al-dalail de Darwish (acheté de Samuelian)
Keywords: Catalogue – Leiden

Inventory of the Oriental Manuscripts of the Library of the University of Leiden. Manuscripts OR. 14001- OR. 15000 registered in Leiden University Library in the Period between 1973-1980 - Witkam, Jan Just (Ter Lugt Press, 2007)
OR 14005 Kitab al-Sira wa akhbar al-a'imma OR 14012 Collection of texts in Arabic, all converning the history of Warglan (Ouargla) OR 14066 OR 14168 OR 14185 حاشية الجامع الصحيح OR 14551 nawazil Nafusa OR 14552 Kitab al-Jirahat OR 14550 Extrait d'El-Mouroud des cheikhs ibadites
Keywords: Catalogue – Leiden

Inventory of the Oriental Manuscripts of the Library of the University of Leiden. Manuscripts OR. 1001- OR. 2000 registered in Leiden University Library in the Period between 1665-1871 - Witkam, Jan Just (Ter Lugt Press, 2007)
OR 1645 III The French Text is by Humbert and in it relates how he registered five types of Arabic Numerals, according to information which he had obtained in 1818 from an inhabitant of the isle of Jerba.
Keywords: Catalogue – Leiden